2014
DOI: 10.1007/s00262-014-1586-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel T cell receptor single-chain signaling complex mediates antigen-specific T cell activity and tumor control

Abstract: Adoptive transfer of genetically modified T cells to treat cancer has shown promise in several clinical trials. Two main strategies have been applied to redirect T cells against cancer: 1) introduction of a full-length T cell receptor (TCR) specific for a tumor-associated peptide-MHC, or 2) introduction of a chimeric antigen receptor (CAR), including an antibody fragment specific for a tumor cell surface antigen, linked intracellularly to T cell signaling domains. Each strategy has advantages and disadvantages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 57 publications
0
36
0
Order By: Relevance
“…Retroviral supernatants were harvested after 48 h and 58 −/− cells were transduced as described previously (Stone et al, 2014). After cells were transduced they were sorted via FACS for binding to MART1/HLA-A2 tetramer to obtain a positive staining population.…”
Section: Methodsmentioning
confidence: 99%
“…Retroviral supernatants were harvested after 48 h and 58 −/− cells were transduced as described previously (Stone et al, 2014). After cells were transduced they were sorted via FACS for binding to MART1/HLA-A2 tetramer to obtain a positive staining population.…”
Section: Methodsmentioning
confidence: 99%
“…While the many parameters that differ between TCRs and CARs (affinity, ligand structure, and ligand density) have made it difficult to compare directly, a system has been developed that allows comparisons by using the analog of a scFv, a single-chain TCR (Vβ-linker-Vα) as a CAR-like receptor [76,77]. This allows the same V regions to be used in a conventional full-length αβ TCR for comparison with the CAR, where the affinity of the cell-associated forms, the ligand (pepMHC), and ligand density are identical.…”
Section: Sensitivity Of Tcrs and Cars: Impact Of Affinity Receptor Dmentioning
confidence: 99%
“…This system also allowed the direct measurement of CAR affinity using typical monomeric pepMHC antigens, and it enables the rapid analysis of the effects of antigen density by simply ‘loading’ different concentrations of peptides onto MHC-positive target cells. Using a high-affinity variant of the 2C TCR called m33 (K d of the TCR and CAR on T cells was identical), it was observed that, in primary CD4 + T cells, the full-length TCR had greater sensitivity to pepMHC than the CAR format (with either CD28 or 4-1BB, and CD3ζ), even though the CAR format was expressed at higher densities on the surface of T cells [77]. Thus, even in the absence of the CD8 coreceptor, the TCR machinery has greater sensitivity.…”
Section: Sensitivity Of Tcrs and Cars: Impact Of Affinity Receptor Dmentioning
confidence: 99%
“…K D values of 1 µM or less) are required to mediate activation in CD4 + T cells as compared to CD8 + T cells, where CD8 can co-engage the class I MHC molecule. Effector CD4 + T cells with higher affinity TCRs have mediated significant tumor control, and in some cases rejections, in mouse models [11,1719]. TCRs with increased affinity against MART1/HLA-A2 [8], NY-ESO-1/HLA-A2 [20], MAGE-A3/HLA-A2 [21], and MAGE-A3/HLA-A1 [22], and ability to mediate in vitro CD4 + T cell activity, have been evaluated in adoptive T cell transfer studies.…”
Section: Tcr Affinities For Self-protein Epitopesmentioning
confidence: 99%